Special issue title: Optimization and mathematical modeling in energy systems - Saharidis, Georgios K.D.; Moza, Zoi; Golias, Mihalis (My University, 2021)
Optimization and mathematical modeling has been successfully used in a variety of applications in the field of Energy Systems. In this Special Volume on optimization and mathematical modeling in energy systems, a variety of research results in different disciplines are included. The electrical energy storage, the resource efficiency of a base camps, the forecasting of energy exports, the wind energy, the optimal management and scheduling of micro grids optimal, the electricity expansion investment problem, the seismic response of a slope earth with embedded pipeline, and the battery deployment strategy, are investigated.
Keywords: energy systems; mathematical modeling